Pengaruh Kegiatan Drum Band untuk Meningkatkan Kecerdasan Musikal pada Anak Usia Dini - Helen Putri Yani; Wiwinda Wiwinda; Evi Selva Nirwana (Journal of Elementary School (JOES), 2023)
The purpose of this study was to determine the effect of drum band activities to improve musical intelligence in early childhood in Hang Tuah Kindergarten, Bengkulu City. The type of research used is quantitative research with a quasi-experimental approach using the Pretest-Posttest Control Group Design. Based on data analysis and discussion of research results, it can be concluded that drum band activities have proven to have an effect on early childhood musical intelligence in Hang Tuah Kindergarten, Bengkulu City. This can be seen from the results of the pretest and posttest experimental and control groups at the time of the study proved to have increased. In the experimental treatment, there was an increase of 80% from the previous pretest result of 30% with the treatment using the drum band musical instrument playing method to an increase of 90%. When the treatment did not use the method of playing musical instruments, it decreased by 55%. Keywords: Drum Band Musical Instruments, Musical Intelligence